An energy efficiency cooperating base station sleep mechanism in LTE-Advanced network - Jihong ZHAO; Jiangyan HU; Hua QU; Wei WANG (Dianxin kexue)
Shut down underutilized base station is a promising approach to reduce energy consumption of network during its off-peak time. The users in sleeping cell were served by neighboring cells，thus avoiding base station transmit power consumption caused by cell range expansion. Base station sleeping technique was combined with CoMP transmission to improve system performance，fully considered power consumption in the cooperative processing，and a scheme of dynamic clustering and base station sleeping to minimize power consumption was proposed. This scheme could select the best cluster to meet each user’s QoS requirement and minimize system power consumption. Simulation results show that the proposed scheme is better than traditional base station sleeping scheme in improving energy efficiency.